1989
DOI: 10.1177/00220345890680081101
|View full text |Cite
|
Sign up to set email alerts
|

A Three-dimensional Evaluation of the Effects of Functional Occlusal Forces on the Morphology of Dental and Periodontal Tissues of the Rat Incisor

Abstract: We examined the effect of function on tooth and periodontal ligament (PDL) morphology in 40 lower incisors of adult female rats. Ten teeth were exposed to occlusal hyperfunction for three months, ten to hypofunction for three weeks, ten to hypofunction for three months, while ten teeth in normal occlusion served as control. Transverse ground sections were cut at various levels perpendicular to the tooth long axis, and their distances from the apex were calculated. The outlines of the tissues were traced and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
9

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 22 publications
1
24
0
9
Order By: Relevance
“…Thus, it was found that adaptations occur in the craniofacial skeleton in response to altered functional stress (Washburn, 1947;Avis, 1961;Kreiborg et al, 1978;Schneiderman and Carlson, 1985). The dental supporting structures also react to changes in functional demands, and it has been shown that decreased or increased function causes dimensional changes in the periodontal ligament (PDL) (Kronfeld, 1931;Coolidge, 1938;Grant et al, 1979;Bondevik, 1984;Steigman et al, 1989). Other studies reported significant changes in tooth morphology of the rat as a result of disrupted eruption (Berkovitz, 1972;Steigman et al, 1983Steigman et al, , 1988 or of altered function (Steigman et al, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was found that adaptations occur in the craniofacial skeleton in response to altered functional stress (Washburn, 1947;Avis, 1961;Kreiborg et al, 1978;Schneiderman and Carlson, 1985). The dental supporting structures also react to changes in functional demands, and it has been shown that decreased or increased function causes dimensional changes in the periodontal ligament (PDL) (Kronfeld, 1931;Coolidge, 1938;Grant et al, 1979;Bondevik, 1984;Steigman et al, 1989). Other studies reported significant changes in tooth morphology of the rat as a result of disrupted eruption (Berkovitz, 1972;Steigman et al, 1983Steigman et al, , 1988 or of altered function (Steigman et al, 1989).…”
mentioning
confidence: 99%
“…The dental supporting structures also react to changes in functional demands, and it has been shown that decreased or increased function causes dimensional changes in the periodontal ligament (PDL) (Kronfeld, 1931;Coolidge, 1938;Grant et al, 1979;Bondevik, 1984;Steigman et al, 1989). Other studies reported significant changes in tooth morphology of the rat as a result of disrupted eruption (Berkovitz, 1972;Steigman et al, 1983Steigman et al, , 1988 or of altered function (Steigman et al, 1989). No information is available, however, about a possible change in the location of the lower incisor within the mandibular border following increased or decreased functional loads.…”
mentioning
confidence: 99%
“…However, this decrease in area density may not reflect an actual decrease in the total number of fibers. In rat incisors after 3 months of hypofunction, a significant increase was observed in the cross-sectional area of the socket, but this increase was not significant after 3 weeks of hypofunction (Steigman et al, 1989). The figures of region 1 (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The eruption of these teeth was in an unimpeded or hypofunctional condition. The contralateral incisors were impeded, occluding with both upper incisors, thus in a hyperfunctional condition (Steigman et al, 1989). The lower incisors of the remaining nine rats were kept during the period in normofunctional conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In the interrupted condition, the eruption rate was markedly interrupted (&10 fold less than that of the normal eruption group), in agreement with a previous study from our laboratory (Neves et al 2009), confirming that the immobilization by steel wire efficiently impeded the incisor eruption. Steigman et al (1989) studied the incisor under hypofunction eruption conditions, in which there is an increase in the eruption rate, reported some morphological alterations such as variation in tooth size components (decreased dentin and increased pulp size). In contrast, in the present study, the incisor tooth was immobilized to interrupt the eruption and, in this condition, we demonstrated for the first time, visible alterations in the morphology of the tooth germ and socket area.…”
Section: Discussionmentioning
confidence: 99%